Data from: Larger fragments have more late-successional species of woody plants than smaller fragments after 50 years of secondary succession - Liu, Jiajia; Coomes, David; Hu, Guang; Liu, Jinliang; Yu, Jingjing; Luo, Yangqing; Yu, Mingjian; Coomes, David A. (Dryad, 2019)
1. Most fragmentation research focuses on the effects of carving up
old-growth forests, but less is known about influences of habitat
fragmentation on secondary succession in patches of regenerating forests.
2. Working with forest dynamics on islands in a vast lake created by a
hydroelectric dam in China (the Thousand Island Lake), we sampled 29
islands that were cleared of forest during dam construction in 1959 and
then underwent succession. Measurements taken in 2009-2010 and 2014-2015
evaluated community assembly during succession, based on species
diversity, functional traits and structural properties. 3. Forests on
small islands remained at relatively early stages of compositional
succession: species richness was low, and communities were dominated by
early-successional species, with few animal-dispersed and shade-tolerant
plants. However, these islands had accumulated similar aboveground biomass
density to that on larger islands, mostly in the stems of a fast-growing
pine species. Island size was the key driver of secondary succession in
regenerating forest fragments, while isolation had comparatively little
effect. Edge effects were important for species composition and functional
composition. 4. Synthesis: Habitat fragmentation resulting from the
creation of an artificial lake affected community assembly, with fewer
late-successional species on smaller islands. Maintenance of large
fragments is critical for the rapid succession of forests. Paradigms on
habitat fragmentation effects drawn from old-growth forest studies are
unlikely to hold in regenerating forest fragments. Restoration activities
should consider landscape patterns to accelerate secondary succession of
regenerating forests.
Thousand Island lake 2009-2010 plot datasets
Keywords: Colonisation; 2009-2010; old-growth forest; 2014-2015; forest fragmentation; edge effect